A simulation model for predicting the temperature during the application of MR-guided focused ultrasound for stroke treatment using pulsed ultrasound - Damianou, Christakis A.; Hadjisavvas, V. (My University, 2011)
In this paper a simulation model for predicting the temperature during the application of MR-guided focused ultrasound for stroke treatment using pulsed ultrasound is presented. A single element spherically focused transducer of 5 cm diameter, focusing at 10 cm and operating at either 0.5 MHz or 1 MHz was considered. The power field was estimated using the KZK model. The temperature was estimated using the bioheat equation. The goal was to extract the acoustic parameters (power, pulse duration, duty factor and pulse repetition frequency) that maintain a temperature increase of less than 1°C during the application of a pulse ultrasound protocol. It was found that the temperature change increases linearly with duty factor. The higher the power, the lower the duty factor needed to keep the temperature change to the safe limit of 1°C. The higher the frequency the lower the duty factor needed to keep the temperature change to the safe limit of 1°C. Finally, the deeper the target, the higher the duty factor needed to keep the temperature change to the safe limit of 1°C. The simulation model was tested in brain tissue during the application of pulse ultrasound and the measured temperature was in close agreement with the simulated temperature. This simulation model is considered to be very useful tool for providing acoustic parameters (frequency, power, duty factor, pulse repetition frequency) during the application of pulsed ultrasound at various depths in tissue so that a safe temperature is maintained during the treatment. This model could be tested soon during stroke clinical trials. © 2011 American Institute of Physics.
Keywords: Duty factor; Focal depth; Pulsed ultrasound